Penerapan Semiotika Roland Barthes sebagai Strategi Pengembangan Analisis Kritis di Lembaga Kajian Dialektika - Nurul Ashri (Universitas Pamulang, 2025)
The need for critical analytical tools in examining cultural, literary, and media phenomena has grown significantly in response to the rapid flow of information in the digital era. Roland Barthes’ semiotics, particularly the concepts of denotation, connotation, and myth, offers a highly relevant methodological framework for uncovering the layered meanings of texts and cultural representations. This community service activity aimed to enhance the analytical capacity of members of the Lembaga Kajian Dialektika through training on Barthes’ semiotic approach. The program was designed as an interactive workshop consisting of theoretical lectures, group discussions, case studies, and hands-on analysis of both literary and media texts. The activity was conducted online via Zoom on June 15, 2025. The results indicate a high level of enthusiasm and active engagement among participants during discussions and analytical practices. Participants successfully identified differences between denotative and connotative meanings and gained an understanding of how myths are constructed within media texts. Prior to the training, most participants relied on descriptive approaches, but afterward, they demonstrated a more critical orientation in interpreting cultural representations. The main challenges encountered were time limitations and participants’ varied methodological backgrounds. Overall, the training significantly broadened the methodological perspectives of the participants while strengthening the tradition of critical inquiry within the institution. Future recommendations include advanced training programs that incorporate contemporary semiotics, hermeneutics, and critical theory in order to further develop participants’ analytical capacities.